Réponses

2013-03-02T17:51:31+01:00
A) -3(u+2v)-2(u+v) =
-3u-6v-2u-2v =
-5u-8v

B) -5u+2(-3u+v)-5(u-2v)=
-5u-6u+2v-5u+10v=
-16u+12v.

C) 2/5u+3/4u-1/2u=
13/3u

D) 1/2(2u+2/3v)-(-u+2/3v)=
1u+1/3v+u-2/3v=
2u-1/3v.
Meilleure réponse !
2013-03-02T18:31:33+01:00

a. -3(u+2v) - 2(u+v) = -3u - 6v - 2u - 2v

                                   = -5u - 8v


b. -5u + 2(-3u+v) - 5(u-2v) = -5u - 6u + 2v - 5u + 10v

                                               = -16u + 12v


c. 2/5u + 3/4u -1/2u = 8/20 u + 15/20 u - 10/20 u

                                    = 13/20 u

 
d. 1/2(2u+2/3v) - (-u+2/3v) = u + 1/3 v + u - 2/3 v

                                               = 2u - 1/3 v